2012
DOI: 10.1016/j.vaccine.2012.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and vulnerability and serologic response to influenza vaccination in older adults

Abstract: Background Serologic response to influenza vaccination declines with age. Few other host factors are known to be associated with serologic response. Our objective was to determine whether obesity and vulnerability independently predicted serologic response to influenza vaccination. Methods Adults ≥ 50 yrs were recruited during the 2008-09 influenza season. Subjects provided pre- and post-vaccination sera for measuring antibody titers to 2008-09 vaccine components. Body mass index (BMI) was calculated as weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 28 publications
5
65
1
5
Order By: Relevance
“…Day 0 magnesium and phosphorus levels were also significantly related to immune response to A/H1N1 levels when being overweight was included in the model. Other research has reported no relationship of obesity to immune response to influenza vaccine, 13 The major finding of the current study is the strong association between Day 21 phosphorus levels and both Day 21 seroprotection and seroconversion for both influenza A strains. The literature suggests a prominent role for phosphorus for lymphocyte and monocyte proliferation and activation.…”
Section: Discussionsupporting
confidence: 49%
“…Day 0 magnesium and phosphorus levels were also significantly related to immune response to A/H1N1 levels when being overweight was included in the model. Other research has reported no relationship of obesity to immune response to influenza vaccine, 13 The major finding of the current study is the strong association between Day 21 phosphorus levels and both Day 21 seroprotection and seroconversion for both influenza A strains. The literature suggests a prominent role for phosphorus for lymphocyte and monocyte proliferation and activation.…”
Section: Discussionsupporting
confidence: 49%
“…49 But it should be noted that even in the published reports, BMI was not correlated with antibody levels at 3 mo post-immunization, only later at one year when a differential decline was detected by Sheridan et al 49 Our findings appear to concur with another study that also investigated the 2009-10 influenza vaccine, which failed to find a correlation between antibody responses and BMI. 50 Similarly, we were unable to detect a correlation between obesity and virus-specific cytokine production. 49 Most significantly, our study did not replicate the findings of Davidson and colleagues, who reported positive effects of MBSR on the incremental rise in IgG to influenza vaccination from month 1 to month 2.…”
Section: Discussionmentioning
confidence: 64%
“…13 This study benefitted from a high degree of similarity among the study groups, effectively controlling for a range of potential influences on responses to vaccination including age, 19 sex, prior influenza vaccination, 15,16 frailty, 20 chronic health conditions, obesity, 21 moderate exercise 22 and probiotic use. 23 Similarity of baseline antibody titers among the study groups avoided the need for adjustment of observed responses.…”
Section: Discussionmentioning
confidence: 99%